Pattern of paediatric HIV status disclosure in coastal Karnataka - Nishanth Krishna Kodyalamoole (Indian Journal of Medical Research, 2018)
Background & objectives: Karnataka is a high HIV prevalent State in India. Although benefits have been shown by disclosing the HIV status to the child, information regarding HIV status disclosure in Karnataka is limited. Hence, this study was conducted to estimate the proportion of children who had been disclosed of their HIV status and its pattern among those who visited the district antiretroviral therapy (ART) centre in coastal Karnataka. Methods: A cross-sectional study was conducted in an ART centre in a district hospital in coastal Karnataka between October 2014 and July 2015. Caregivers of paediatric HIV patients were approached and willing participants were administered a pre-formed, pre-tested semi-structured questionnaire developed for the study. Results: A total of 185 caregivers of the HIV-positive children were interviewed. Mean age of the children was 11±4 years. Only 107 (57.8%) children were aware of their HIV status. Of these, 95 were disclosed fully. Counsellors in rehabilitation centres were the most probable person to disclose and planned events. Children were told of their HIV status for their knowledge and were more likely to be disclosed if they were around 11-15 yr of age and staying in rehabilitation centres. Interpretation & conclusions: Older children were more likely to be disclosed of their HIV status by counsellors. Steps need to be taken to counsel and encourage caregivers to fully disclose the HIV status to the children at least when they attain the age more than 11 years.